2007
DOI: 10.1016/j.nurt.2007.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Magnetic Resonance Neurospectroscopy

Abstract: Summary:Over the past two decades, proton magnetic resonance spectroscopy (proton MRS) of the brain has made the transition from research tool to a clinically useful modality. In this review, we first describe the localization methods currently used in MRS studies of the brain and discuss the technical and practical factors that determine the applicability of the methods to particular clinical studies. We also describe each of the resonances detected by localized solvent-suppressed proton MRS of the brain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 201 publications
(175 reference statements)
2
64
0
Order By: Relevance
“…Altered mI is usually interpreted to indicate as glial activation and macrophage infiltration 29 . The change in mI levels post irradiation in our study supports biochemical alterations associated with neuroinflammatory response of glial cells 30 . Several studies have supported another hypothesis that radiation induced injury is driven in part, via increased oxidative stress through generation of free radicals [31][32][33] .…”
Section: Discussionsupporting
confidence: 85%
“…Altered mI is usually interpreted to indicate as glial activation and macrophage infiltration 29 . The change in mI levels post irradiation in our study supports biochemical alterations associated with neuroinflammatory response of glial cells 30 . Several studies have supported another hypothesis that radiation induced injury is driven in part, via increased oxidative stress through generation of free radicals [31][32][33] .…”
Section: Discussionsupporting
confidence: 85%
“…The utility of NAA, as an axonal marker is supported by the loss of NAA in many white matter diseases, including leukodystrophies [11], multiple sclerosis (MS) [12] and hypoxic encephalopathy [13], chronic stages of stoke [14] and tumors [1,2,9]. However, there are cases when the abnormal levels of NAA do not reflect changes in neuronal density, but rather a perturbation of the synthetic and degradation pathways of NAA metabolism.…”
Section: Neurospectroscopy Biochemical Features and Their Clinical Simentioning
confidence: 99%
“…The reader is referred to two recent reviews in this journal that include a discussion of the technical aspects of MRS. 55,56 Proton MRS studies have revealed that myriad brain metabolite concentrations including N-acetylaspartate (NAA), choline (Cho), lactate (Lac), lipids, myoinositol (mI), and glutamate/glutamine are altered in patients with MS and undergo longitudinal change. 55,57,58 Individual metabolites are believed to reflect specific underlying pathologies.…”
Section: Mrsmentioning
confidence: 99%